2022
DOI: 10.1111/opo.13035
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations and temporal trends of childhood myopia prevalence in Africa: A systematic review and meta‐analysis

Abstract: Purpose To provide contemporary and future estimates of childhood myopia prevalence in Africa. Methods A systematic online literature search was conducted for articles on childhood (≤18 years) myopia (spherical equivalent [SE] ≤ −0.50D; high myopia: SE ≤ −6.00D) in Africa. Population‐ or school‐based cross‐sectional studies published from 1 Jan 2000 to 30 May 2021 were included. Meta‐analysis using Freeman–Tukey double arcsine transformation was performed to estimate the prevalence of childhood myopia and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 119 publications
(266 reference statements)
1
6
0
Order By: Relevance
“…The finding of this meta-analysis (5.26%) is consistent with the results of meta-analyses done in children in India in 2018 (5.3%) 60 and Nepal in 2023 (7.1%). 61 It is also in line with the result of a meta-analysis of childhood myopia and myopia in school children in Africa in 2022 (4.7%) 12 , 62 and comparable with the study finding in Ethiopia among school students (5.10%), 13 based on the results of 16 articles. The similarity in the study results may be due to approximate similarities in the study populations specifically their age.…”
Section: Discussionsupporting
confidence: 88%
“…The finding of this meta-analysis (5.26%) is consistent with the results of meta-analyses done in children in India in 2018 (5.3%) 60 and Nepal in 2023 (7.1%). 61 It is also in line with the result of a meta-analysis of childhood myopia and myopia in school children in Africa in 2022 (4.7%) 12 , 62 and comparable with the study finding in Ethiopia among school students (5.10%), 13 based on the results of 16 articles. The similarity in the study results may be due to approximate similarities in the study populations specifically their age.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to studies that generalized to simple urban-rural divisions, Zhang et al found that average population density in administrative divisions was associated with myopia risk among Chinese children independent of factors such as academic activities, outdoor time, family educational level, and economic development. Similarly, studies conducted in Africa projected an increase in childhood myopia prevalence in urban settings . Additionally, the presence of green spaces within school campuses is associated with a lower prevalence of myopia at the school level and potentially with reduced risk of myopia development in individuals .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies conducted in Africa projected an increase in childhood myopia prevalence in urban settings. 30 Additionally, the presence of green spaces within school campuses is associated with a lower prevalence of myopia at the school level and potentially with reduced risk of myopia development in individuals. 17 , 18 In our study, we systematically examined various environmental variables with population density as a reference point.…”
Section: Discussionmentioning
confidence: 99%
“…General inclusion criteria, as determined at the baseline visit, were as follows: (1) between 6 and <9 years of age; (2) uncorrected distance visual acuity (VA) of 0.1 LogMAR or better in each eye and (3) refractive error (spherical equivalent, M, determined by cycloplegic open-field autorefraction) of no less than −0.25D and no more than +2.50D in the right eye, with less than or equal to 0.75D of anisometropia or 0.75D of astigmatism in either eye (determined by cycloplegic open-field autorefraction).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Myopia is a major public health concern precipitated by its increasing prevalence worldwide 1–7 and the associated risk of potentially blinding conditions 8–12 . Projections indicate that by the year 2050, over half of the world's population will have myopia, with 10% of those having high myopia 13 .…”
Section: Introductionmentioning
confidence: 99%